UPAYA MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA MELALUI MODEL QUANTUM LEARNING PADA MATA PELAJARAN IPA MATERI PENYESIAIAN DIRI MAKHLUK HIDUP KELAS V SD MUHAMMADIYAH BAUSASRAN - Cahyo, Hendi Dwi; Maryani, Ika (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2018)
The material taught at this time is increasingly difficult, the way to teach teachers is still conventional, the lack of media and learning facilities, especially in science learning which requires concrete understanding. This study aims to improve motivation and learning outcomes in science lessons through Quantum Learning for fifth grade students at SD Muhammadiyah Bausasran. The subjects in this study were fifth grade students of SD Muhammadiyah Bausasran. The object in this study is the motivation and learning outcomes of science using the Quantum Learning model. Data collection techniques used in the form of observation, tests, and interviews. While the analysis technique uses descriptive quantitative. The research carried out belongs to the type of Class Action Research which consists of two cycles. The criteria for success of action in this study are seen from the increase in motivation and learning outcomes of science using Quantum Learning. The results showed that the activities and learning outcomes of science used Quantum Learning models from cycle I and Cycle II experienced an increase. The results of observation of motivation of students in the first cycle of the first meeting the percentage value of 35.33% reached the criteria of "low", the second meeting obtained a percentage of 45.44% which reached the criteria of "sufficient". In the second cycle the first meeting percentage was 68.76% and reached the criteria of "high" while the second meeting received a percentage of 93.95% with the criteria of "very high". Whereas in the learning outcomes of students of science subjects using the Quantum Learning model based on the results of the pretest and posttest conducted the results obtained in the first cycle the percentage completeness of the class from the first cycle of the first meeting was 8.33%, while the second meeting was 33.33%. In the second cycle the first meeting became 79.17% and at the second meeting it became 95.83%. The results of the percentage of completeness have reached the completeness value> 70%.